Sustainable cities and communities – Best practices for structuring a SDG model. (August 2019) - Neumann, K
Abstract: The UN's SDGs are powerful beacons to a better world yet some of their targets remain vague for the sake of special interest groups. They are sometimes synergetic and quite often ambivalent. On a concrete operative level it is therefore a challenge to plan for them fostering synergetic measures and minimizing trade-offs. Since many concrete projects that go for the SDGs are rather unique and need to consider many stakeholders, the systemic approach of a participatory explorative cause and effect modeling should be applied in order to tackle the underlying complexity of these projects. On the example of SDG 11 and with the use of the software iMODELER the approach is presented offering some best practice for structuring a SDG model, facilitating participatory stakeholder workshops, identifying levers for successful action, and establishing a culture of reflection. Although this approach has been applied successfully in Africa as well as in Germany it is also crucial to prevent typical hindrances. A kind of template for a model structure will be presented for both, a town in a developing country and a town in an industrialized country.